2006
DOI: 10.1111/j.1474-9726.2006.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction mimetics: an emerging research field

Abstract: SummaryWhen considering all possible aging interventions evaluated to date, it is clear that calorie restriction (CR) remains the most robust. Studies in numerous species have demonstrated that reduction of calories 30-50% below ad libitum levels of a nutritious diet can increase lifespan, reduce the incidence and delay the onset of age-related diseases, improve stress resistance, and decelerate functional decline. A current major focus of this research area is whether this nutritional intervention is relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
277
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(286 citation statements)
references
References 113 publications
5
277
0
4
Order By: Relevance
“…compounds that can capture the benefits of DR without the requirement for chronic food restriction. A whole host of putative DR mimetics have been reviewed in detail elsewhere (83)(84)(85)(86) , but this review will concentrate on three compounds currently enjoying much of the limelight as plausible DR mimetics; rapamycin, metformin and resveratrol.…”
Section: Dietary Restriction Mimeticsmentioning
confidence: 99%
“…compounds that can capture the benefits of DR without the requirement for chronic food restriction. A whole host of putative DR mimetics have been reviewed in detail elsewhere (83)(84)(85)(86) , but this review will concentrate on three compounds currently enjoying much of the limelight as plausible DR mimetics; rapamycin, metformin and resveratrol.…”
Section: Dietary Restriction Mimeticsmentioning
confidence: 99%
“…When activated, AMPK negatively regulates mTOR activation (Mihaylova and Shaw 2011). AMPK activation slows aging in C. elegans (Apfeld et al 2004;Mair et al 2011) and is being considered as a calorie restriction mimetic (Ingram et al 2006). Therefore, metformin has been used for life extension in mammals and, in some studies although not all, has demonstrated gerosuppressive effects (Smith et al 2010;Anisimov et al 2011;Berstein 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Calorie restriction (CR) is the only experimental manipulation that is known to extend the lifespan of a number of organisms including yeast, worms, flies, rodents (Ingram et al 2006). In addition, CR has been shown to reduce the incidence of age-related disorders (for example, diabetes, cancer, and cardiovascular disorders) in mammals (Willcox et al 2007).Whether this occurs in longer-lived species is unknown, although the effect of prolonged calorie restriction in nonhuman primates is under investigation (Fontana et al 2004;Sinclair 2005).…”
Section: Introductionmentioning
confidence: 99%